Carbon Credit and its Relevance in the Present Scenario: A Study from the Indian Perspective - Dutta, Sujit (Prabandhan: Indian Journal of Management, 2015)
There is an emerging global consensus that fighting climate change is a major challenge of the 21st century. Changes in the global environment are increasingly challenging businesses around the world. Companies are now expected to integrate environmental concerns into their strategic management. The emergence and popularization of the international climate change debate has created an increasingly relevant focus upon the potential of low carbon opportunities within the corporate sector. Presently, there is a need for awareness of carbon trading since it is a key policy instrument for low carbon business growth. The importance of carbon credit trading is significant in an emerging economy like India. Accordingly, the study analyzed the relevance of carbon credit trading in India as well as the opportunities to reduce carbon footprints, which can even help to improve the bottom line of organizations.